Effect of nickel on hydrogen permeation in ferritic/pearlitic low alloy steels - Iannuzzi, Mariano; Husby, H.; Johnsen, R.; Kappes, M.; Barnoush, A. (Elsevier Ltd, 2018)
Nickel offers several beneficial effects as an alloying element to low alloy steels. However, it is, in the oil and gas industry, limited by part 2 of the ISO 15156 standard to a maximum of 1 wt% due to sulfide stress cracking resistance concerns. Hydrogen uptake, diffusion, and trapping were investigated in research-grade ferritic/pearlitic low alloy steels with Ni contents of 0, 1, 2 and 3 wt% by the electrochemical permeation method as a function of temperature and hydrogen charging conditions. Qualitatively, the effective diffusion coefficient, Deff, decreased with increasing Ni content. The sub-surface lattice hydrogen concentration, C0, decreased with increasing Ni content in all charging conditions while the trend between the sub-surface hydrogen concentration in lattice and reversible trap sites, COR, and Ni content varied with the charging conditions. Irreversible trapping, evaluated by consecutive charging transients, was not observed for any of the materials. Lastly, the possible influence of an increasing fraction of pearlite with increasing Ni content is discussed.